Complete Genome Sequence of Agrobacterium tumefaciens 1D1609 - Haryono, Mindia (Genome Announc, 2018)
Agrobacterium tumefaciens 1D1609 is a highly virulent strain isolated from a crown gall tumor of alfalfa (Medicago sativa L.). Compared to other well-characterized A. tumefaciens strains, such as C58 and Ach5, 1D1609 has a distinctive host range. Here, we report its complete genome sequence to facilitate future studies.